Mentoring in teacher training: Identity and professional development (Revista Contexto & Educação, 2025)
This article explores the role of mentoring in teachers' professional development, using a qualitative bibliographic research of the 'state of knowledge' type. Discursive textual analysis (DTA) was used to interpret data collected from databases such as BDTD and Scielo, focusing on descriptors such as 'mentoring', 'academic mentoring' and 'teacher training'. The research revealed an initial scarcity of studies on mentoring in undergraduate courses, requiring adjustments to the inclusion criteria. It was observed that mentoring is more common in the health field, especially in medicine and nursing, with an increase in publications on mentoring in education between 2013 and 2024. The selected works sought to understand the different conceptions of mentoring applied to education. The choice of DTA allowed an in-depth analysis of the meanings present in the texts, expanding the understanding of the theme. The researchers highlight the potential of mentoring in teacher training, based on its successful application in other areas and records of its use in basic education. However, they emphasize the need for more research on mentoring in undergraduate courses in Brazil. In conclusion, mentoring can strengthen teacher training and promote a more humane education, but the importance of investing in the teacher's career beyond initial training is emphasized.
Keywords: Mentoring and mentoring in teacher training; Professional development; Blended Learning, Teacher Training, Learning in the Digital Teaching, Professional and technological education